Implementasi Penerimaan Tahanan Pada Masa Transisi ‎ Menuju Endemi Di Lapas Perempuan Kelas II A Kerobokan - Rahayu Intan Mandasari; Deli Bunga Saravistha; Komang Edy Dharma Saputra (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
This study discussed the implementation of prison admission during the transitional period towards endemic at Class II A Kerobokan Women's Prison. The situation in different elements of the world community's life, particularly in Indonesia, is gradually improving because the country has entered a transitional stage into endemic status. This condition is one of the factors considered by the government when enacting new policies, such as the Adjustment of Correctional Services by the Ministry of Law and Human Rights of the Republic of Indonesia. The purpose of this study was to examine how prison admission was implemented at Class II A Kerobokan Women's Prison during the transitioning period to endemic. The empirical legal research method was adopted, with a direct approach to the field. In this study, the authors found out that the implementation of prison admission during the transition to endemic period still referred to the Decree of the Director General of Corrections Ministry of Law and Human Rights of the Republic of Indonesia Number: PAS-170.PK.01.01.02 of 2015 concerning Standards for Registration and Classification of Prisoners and Detainees. The prison admission remained in accordance with the Standard Operating Procedures (SOP) contained in the regulation. However, there are several adjustments due to the transition period which has been listed in the Decree of the Director General of Corrections of the Ministry of Law and Human Rights of the Republic of Indonesia Number PAS-04.OT.02.02 of 2023 concerning Adjustments to the Implementation of Correctional Services During the Transitional Period Towards Endemic. Several additional provisions that apply include admission carried out in stages considering the occupancy capacity equipped with rapid or swab letters with non-reactive results, carrying out health screening according to procedures, and continuing to carry out intensive coordination with Law Enforcement Officials, the local Covid-19 Task Force, and stakeholders.